Observing mixed layer depth, nitrate and chlorophyll concentrations in the northwestern Mediterranean: A combined satellite and NO3 profiling floats experiment. Issue 18 (23rd September 2014) - D'Ortenzio, Fabrizio; Lavigne, Hélöise; Besson, Florent; Claustre, Hervé; Coppola, Laurent; Garcia, Nicole; Laës‐Huon, Agathe; Le Reste, Serge; Malardé, Damien; Migon, Christophe; Morin, Pascal; Mortier, Laurent; et al.
Abstract Two profiling floats, equipped with nitrate concentration sensors were deployed in the northwestern Mediterranean from summer 2012 to summer 2013. Satellite ocean color data were extracted to evaluate surface chlorophyll concentration at float locations. Time series of mixed layer depths and nitrate and chlorophyll concentrations were analyzed to characterize the interplay between the physical‐chemical and biological dynamics in the area. Deep convection (mixed layer depth > 1000 m) was observed in January–February, although high‐nitrate surface concentrations could be already observed in December. Chlorophyll increase is observed since December, although high values were observed only in March. The early nitrate availability in subsurface layers, which is likely due to the permanent cyclonic circulation of the area, appears to drive the bloom onset. The additional nitrate supply associated to the deep convection events, although strengthening the overall nitrate uptake, seems decoupled of the December increase of chlorophyll.